(untitled) (Medical Forum Monthly, 2024)
Objective: To determine expression of Ki-67 in Adenoid cystic carcinoma of salivary glands. Study Design: Descriptive study. Place and Duration of Study: This study was conducted at the Department of Oral Pathology, de’Montmorency College of Dentistry, Lahore from May 2014 to December 2016. Materials and Methods: Thirty two cases of Adenoid cystic carcinoma (ADCC) of salivary glands were selected from Departments of Surgery, Lahore General Hospital, Mayo Hospital, and de’Montmorency College of Dentistry, Lahore. Slides were prepared by routine hematoxylin and eosin (H & E) staining, as well as by Immuno-histochemistry (IHC) for Ki-67. Grading of ADCC was done as low, intermediate and high grades on H&E sections. Scoring of Ki-67 expression was determined on Ki-67 immunohistochemical stained slides. Data was entered into SPSS version 22 and descriptive statistics were determined. Results: Out of 32 cases of Adenoid cystic carcinomas 68.1% (22) reported in female and remaining in male (10) 31.2%.Total cases of intermediate grade ADCCs were 43.8%, high grade ADCCs were 31.3%, and low grade ADCCs were 25%. Strong positive expression was observed in 93.8% cases and only 6.3% showed moderate positive expression. A significant association of Ki 67 with grades of Adenoid cystic Carcinoma was observed (p 0.041). Conclusion: Ki-67 is expressed in Adenoid cystic carcinoma. In most of the cases ADCC expressed strong positive expression of Ki-67. Its expression is helpful in grading small biopsies, predicting behavior, and planning target therapy of Adenoid cystic carcinoma.